If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + -1(-37) = 55 Multiply -1 * -37 x + 37 = 55 Reorder the terms: 37 + x = 55 Solving 37 + x = 55 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-37' to each side of the equation. 37 + -37 + x = 55 + -37 Combine like terms: 37 + -37 = 0 0 + x = 55 + -37 x = 55 + -37 Combine like terms: 55 + -37 = 18 x = 18 Simplifying x = 18
| 3ln(2)-2ln(3)=0 | | 48=-4(-3x-6) | | -14=a+24 | | x=3r-12 | | 2(2n+3)=10 | | (-1)x=-10 | | 5x^2+24x+27=0 | | m-16=8 | | 3+3r-4r=-1 | | 3(10-2n)=0 | | 8+y=-7 | | 1.4f+1.1=8.3f | | 26y=32 | | 1.4f+1.1=8.3f | | 2x=-(-8) | | r^2+2r+2=0 | | 4.8=-16+1.6z | | 5(2n+1)=25 | | 0.75w+4=-3(0.75w+2)+8 | | 6x-2(x-2)=9x+4 | | (-2)x=-5 | | 6a^2-13a+5=0 | | -3.8d=8.74-1.9d | | x-(-6)=-80 | | 10(n-2)=100 | | -22=r+3+4r | | [4u-2]=10 | | -17=-5a+7-4 | | 3(9-7)=2(10+9) | | 55-4x=8x+22 | | 5g+4(-5+3g)=1-9 | | x-41=-58 |